2012
DOI: 10.1137/110828551
|View full text |Cite
|
Sign up to set email alerts
|

NR$xx$ Simulation of Microflows with Shakhov Model

Abstract: In this paper, we propose a method to simulate the microflows with Shakhov model using the NRxx method developed in [4,6,5]. The equation under consideration is the Boltzmann equation with force terms and the Shakhov model is adopted to achieve the correct Prandtl number. As the focus of this paper, we derive a uniform framework for different order moment systems on the wall boundary conditions, which is a major difficulty in the moment methods. Numerical examples for both steady and unsteady problems are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 31 publications
(79 reference statements)
0
55
0
Order By: Relevance
“…The G26 results show several improvements over the R13 system at the expense of extended equations. It is also possible to numerically generate large systems of regularized moment equations, as demonstrated by Cai & Li (2010) and Cai et al (2012). In this way, it is possible to approximate the actual solution of the Boltzmann equation quite accurately.…”
Section: Further Systems Of Moment Equationsmentioning
confidence: 99%
“…The G26 results show several improvements over the R13 system at the expense of extended equations. It is also possible to numerically generate large systems of regularized moment equations, as demonstrated by Cai & Li (2010) and Cai et al (2012). In this way, it is possible to approximate the actual solution of the Boltzmann equation quite accurately.…”
Section: Further Systems Of Moment Equationsmentioning
confidence: 99%
“…A list of relevant publications can be found in the references of [13]. Recently we became interested in the large moment system together with its numerical methods [2,3,4,5], and it was found that the lack of the well-posedness due to the loss of global hyperbolicity is a major obstacle in our simulations, especially for large Mach number gas flows [5]. Torrilhon [14] provided a 13-moment moment system based on the multivariate Pearson IV distributions, which is hyperbolic when reduced to one dimension, but it seems unlikely that the same technique can be extended to systems with a large number of moments.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, people are also starting to concentrate on collision models other than the simple Maxwell molecules [31]. It has been shown in [5,6] that BGK and Shakhov collision terms can be easily modeled by the moment method with almost arbitrary number of moments. However, the construction of moment methods with the original collision operator is obviously not so trivial as the BGK and Shakhov operators [33].…”
Section: Introductionmentioning
confidence: 99%